2019
DOI: 10.3390/medicines6020063
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Crude Drugs Used in Japanese Kampo Formulas for Autophagy-Mediated Cell Survival of the Human Hepatocellular Carcinoma Cell Line

Abstract: Background: Autophagy is a catabolic process through which dysfunctional proteins and organelles are degraded, and that is associated with the proliferation of cancer cells. The aim of this study was to screen approximately 130 kinds of crude drugs used in Japanese Kampo formulas to identify crude drugs that would regulate the proliferation through autophagy of human hepatocellular carcinoma HepG2 cells. Methods: Extracts of each crude drug were prepared using methanol. Protein levels were determined using Wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Cell viability was measured using a previously described method [ 20 , 21 , 22 ]. Briefly, cells (0.9 × 10 4 cells/well) were seeded in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell viability was measured using a previously described method [ 20 , 21 , 22 ]. Briefly, cells (0.9 × 10 4 cells/well) were seeded in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…We previously screened approximately 130 crude drugs used in Kampo formulas in a comprehensive search to identify bioactive compounds that regulate autophagy in hepatocellular carcinoma HepG2 cells [ 20 ]. We demonstrated that arctigenin, which is a lignan found in the fruits of Arctium lappa and the fruits of Forsythia suspensa , inhibited cell proliferation and attenuated autophagy in HepG2 cells [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For examples, a mostly recent study performed by Yang and co-authors indicated that autophagy was capable of protecting nucleus pulposus cells from the apoptosis induced cyclic mechanical tension [25]. Autophagy is also reported to potently increase human hepatocellular carcinoma HepG2 cell proliferation, by using this notion, Okubo et al screened approximately 130 kinds of crude drugs to discovery effective crude drugs supporting cell growth via regulating autophagy process [26].…”
Section: Sphk1 Gene Plays An Important Role In a Variety Of Diseases mentioning
confidence: 99%
“…In addition to the aforementioned expectation of future clinical application, knowledge of the detailed mechanisms by which Kampo interferes with autophagy will provide insight into the regulation of autophagy. To date, very few studies have focused on the relationship between Kampo and autophagy [11], [12]. We took advantages of our original tf-LC3 screening system, which could quantitatively estimate the effect of each drug on autophagy [13].…”
Section: Introductionmentioning
confidence: 99%